STUDY OF THE INFLUENCE OF THE MAIN ELEMENTS OF THE PUMPING SYSTEM ON ITS EFFICIENCY (Web of Discoveries: Journal of Analysis and Inventions, 2024)
The article presents the results of energy efficiency research of powerful pumping equipment for water supply. The influence of the main elements of the pumping system on its efficiency is investigated. Reliability of pumps operation is investigated.